2019
DOI: 10.1038/s41419-019-1711-1
|View full text |Cite|
|
Sign up to set email alerts
|

Modified CAR T cells targeting membrane-proximal epitope of mesothelin enhances the antitumor function against large solid tumor

Abstract: Mesothelin (MSLN) is an attractive antigen for chimeric antigen receptor (CAR) T therapy and the epitope selection within MSLN is essential. In this study, we constructed two types of CARs targeting either region I of MSLN (meso1 CAR, also known as a membrane-distal region) or region III of MSLN (meso3 CAR, also known as a membrane-proximal region) using a modified piggyBac transposon system. We reported that, compared with meso1 CAR T cells, meso3 CAR T cells express higher levels of CD107α upon activation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 47 publications
7
80
0
Order By: Relevance
“…In TICS, live cell imaging reveals that cancer cell lysis by primary human lymphocytes in response to PD-1/L1 blocking antibodies initiates after 3 days. This is in contrast to genetic-engineered or cytokine-activated T cells [11][12][13] or NK cells [24], which readily mediate cancer cell killing within hours in vitro, and which therefore may not be as sensitive to inhibition through immune checkpoint molecules. Moreover, the functional and mechanistic involvement of additional lymphocyte subsets upon PD-1/L1 blockade, such as B cells, gamma-delta T cells, and invariant NK cells, can be dissected in TICS.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In TICS, live cell imaging reveals that cancer cell lysis by primary human lymphocytes in response to PD-1/L1 blocking antibodies initiates after 3 days. This is in contrast to genetic-engineered or cytokine-activated T cells [11][12][13] or NK cells [24], which readily mediate cancer cell killing within hours in vitro, and which therefore may not be as sensitive to inhibition through immune checkpoint molecules. Moreover, the functional and mechanistic involvement of additional lymphocyte subsets upon PD-1/L1 blockade, such as B cells, gamma-delta T cells, and invariant NK cells, can be dissected in TICS.…”
Section: Discussionmentioning
confidence: 93%
“…Nonetheless, it is costly and time-consuming to construct these models, which could reduce their broad application. Using in vitro co-culture assays, we and others have utilised chimeric antigen receptors (CARs)-engineered human CD8+ T cells to study their killing mechanisms of human OC cells [11][12][13]. Although the engineered CD8+ T cells are highly potent in killing tumour cells, the requirement of pre-treatment with highdose immune stimulating cytokines may alter the endogenous sensitivity to PD-1/L1-mediated immune suppression.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…At present, efficacy and safety of adoptive T-cell therapies, in particular chimeric antigen receptor-transduced T-cells (CAR-T), in MPM and other solid tumors are under investigation [49,50]. CAR-T-cells directed against mesothelin (MSLN), a glycoprotein expressed on MPM and other solid tumor cells, with a limited presence on normal tissues [51], represent a promising therapeutic option and many efforts have been made to improve their clinical efficacy and safety profile [52,53]. Recently, Adusumilli and colleagues reported the outcome of a phase I clinical trial, NCT02414269, [54,55] on patients with MPM and pleural metastases from lung or breast cancer treated with anti-MSLN CAR-T-cells.…”
Section: Immunotherapy In Mpmmentioning
confidence: 99%
“…The SKOV-3 cell line was obtained from the Cell Bank of the Chinese Academy of Sciences (Shanghai, China), and SKOV-3-luc was established in our laboratory as described previously [11]. Human peripheral blood mononuclear cells (PBMC) from healthy donors were purchased from AllCells (Shanghai, China) and cryopreserved in our laboratory.…”
Section: Cellsmentioning
confidence: 99%
“…Our previous study demonstrated that modi ed CAR-T cells targeting membrane proximal (region III) epitope of mesothelin exhibited strong antitumor activity against various solid tumors [11,12]. Given this, CAR-T cells were generated with the ability to secrete the anti-CD40 antibody that target region III of the mesothelin to potentially achieve a more powerful e cacy.…”
Section: Introductionmentioning
confidence: 99%